Nonlinear aeroelastic behavior of a base-isolated beam under steady wind flow. (March 2020) - Di Nino, Simona; Luongo, Angelo
Abstract: A homogeneous continuous visco-elastic shear-beam, describing the dynamics of base-isolated tall buildings exposed to a uniformly distributed steady wind flow, is studied. The shear beam is constrained at the bottom end by a nonlinear visco-elastic device and free at the top end. The aeroelastic effects, responsible for self-excitation, are evaluated via the quasi-static theory. The occurrence of Hopf bifurcation is detected. Critical and post-critical behavior is analyzed by applying a perturbation scheme. The critical wind velocity and the associated complex galloping mode are found. The steady value of the oscillation amplitude on the stable limit-cycle and its stability are evaluated as function of the mean wind velocity. The mechanical performances of the structure are investigated in according to the effectiveness of the visco-elastic isolation system. A passive controller is proposed to increase the galloping wind velocity and to reduce the amplitude of the limit-cycle.